THE QUALITY INDEX ASSESSMENT OF FLOOD-AFFECTED RICE FIELDS IN THE COASTAL AREA OF BENGKULU, INDONESIA - Sinta Bella; Kartika Utami; Teguh Adiprasetyo; M. Faiz Barchia; Anandyawati (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
Floods can reduce soil quality because the entry of additional material which results in the loss of top soil due to the process of cleaning up flood residues in rice fields. The entry of mud deposits into rice fields can disrupt the balance of nutrients in the soil. This research aims to determine the relationship between the type of flood and the soil quality of coastal rice fields. The research method uses a purposive random sampling survey method.  After having laboratory soil analysis results, the data was then analyzed using Principal Component Analysis and Minimum Data Set. Sea water flood has a Soil Quality Index of 4.30 with good soil quality criteria, while for rice fields affected by river water flooding with an IKT value of 3.77 the soil quality is rather good and areas not affected by flooding have an IKT value of 4.71 with very good quality criteria. The results of the analysis show that the rice fields can be improved by managing rice fields affected by river and sea water flooding in a better way, such as using a good soil management system, using organic fertilizer and liming.